2016
DOI: 10.1371/journal.pntd.0005048
|View full text |Cite
|
Sign up to set email alerts
|

Full Genome Sequence and sfRNA Interferon Antagonist Activity of Zika Virus from Recife, Brazil

Abstract: BackgroundThe outbreak of Zika virus (ZIKV) in the Americas has transformed a previously obscure mosquito-transmitted arbovirus of the Flaviviridae family into a major public health concern. Little is currently known about the evolution and biology of ZIKV and the factors that contribute to the associated pathogenesis. Determining genomic sequences of clinical viral isolates and characterization of elements within these are an important prerequisite to advance our understanding of viral replicative processes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
205
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(210 citation statements)
references
References 63 publications
5
205
0
Order By: Relevance
“…For instance, the 3’UTRs of a number of mosquito-borne flaviviruses produce subgenomic flavivirus RNAs (sfRNAs) that regulate infection (Pijlman et al, 2008). Recently, Akiyama et al, (2016) found that these sfRNAs are produced in a number of cell types during ZIKV infection, supporting the recent findings of Donald et al (Akiyama et al, 2016; Donald et al, 2016). sfRNAs regulate the flaviviral life cycle and contribute to their pathogenicity by a number of mechanisms.…”
supporting
confidence: 76%
“…For instance, the 3’UTRs of a number of mosquito-borne flaviviruses produce subgenomic flavivirus RNAs (sfRNAs) that regulate infection (Pijlman et al, 2008). Recently, Akiyama et al, (2016) found that these sfRNAs are produced in a number of cell types during ZIKV infection, supporting the recent findings of Donald et al (Akiyama et al, 2016; Donald et al, 2016). sfRNAs regulate the flaviviral life cycle and contribute to their pathogenicity by a number of mechanisms.…”
supporting
confidence: 76%
“…This would be in accordance with the findings for DENV, which indicated that certain RNA structure elements in the flavivirus 3′ UTR, like RNA structure duplications, play a role in host adaptation (37, 38). Furthermore, the flavivirus 3′ UTR is the origin of subgenomic flavivirus RNAs (sfRNAs) (3941). It has been reported that sfRNAs exhibit interferon-antagonistic activities (41, 42).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the flavivirus 3′ UTR is the origin of subgenomic flavivirus RNAs (sfRNAs) (3941). It has been reported that sfRNAs exhibit interferon-antagonistic activities (41, 42). In comparison to, e.g., wt West Nile virus, growth of a West Nile virus mutant deficient in producing sfRNA was reduced in wt mouse embryonic fibroblasts (MEFs), while the mutant replicated like the wt virus in IRF3 −/− × IRF7 −/− MEFs as well as in Vero and BHK cells, which are also described to be interferon deficient (39, 42, 43).…”
Section: Discussionmentioning
confidence: 99%
“…: NC012532.1, kindly provided by Dr. Davis Ferreira, Federal University of Rio de Janeiro, Rio de Janeiro, Brazil) was isolated from a rhesus monkey and injected intracerebrally on Swiss mice for several passages [1] and ZIKV BR (Recife/Brazil, ZIKV PE/243, accession no: KX197192.1, kindly provided by Dr. Marli Tenório Cordeiro, Centro de Pesquisas Aggeu Magalhães, Recife, Brazil) was isolated from a patient presenting classical symptoms of ZIKV infection [28]. These viruses were propagated in Vero and C6/36 cells, respectively.…”
Section: Methodsmentioning
confidence: 99%